Harnessing sponge gourd: an alternative source of oil and protein for nutritional security - Tyagi, Ruchi; Bhardwaj, Rakesh; Suneja, Poonam; Sureja, Amish K.; Munshi, Anilabh D.; Arya, Lalit; Riar, Amritbir; Verma, Manjusha (Frontiers in Nutrition, 2023)
Luffa cylindrica (L.) Roem. is an important cucurbit crop that assures food security and dietary diversity among the poor communities. In the present study, seeds of 42 genotypes of Luffa cylindrica were evaluated for their potential use as oil seed crop. Seed moisture, oil and protein content and fatty acids profile were estimated along with total phenol and sugar content. Signiﬁcant differences were observed among the various genotypes where oil content ranged from 15.4–29.8 % and protein 19.9-30.8%. Total phenol content was high 6.43 to 12.84 mg/100 g, which bodes well for the sponge gourd seeds' ability to act as antioxidants. Significant correlation were found between important constituents studied like protein and oil, palmitic acid, stearic acid and oleic acid. Total unsaturated fatty acids were in higher amount comparable to saturated fatty acids signifying the good quality of Luffa seed oil. Our research revealed that the NDSG-1, Pusa Sneha, DSG-95, DSG-98, DSG-108, and DSG-26 genotypes were very nutritious due to their high levels of protein, oleic acid, and oil output. Additionally, selection of traits having considerable correlation will be beneficial and help in improved varietal development for usage as an alternative oilseed crop. Our research sheds light on the nutritional value of sponge gourd seeds and suggests using them as a potential source for oil and protein, particularly in underdeveloped countries.